PERLINDUNGAN HUKUM KORBAN TINDAK PIDANA KEBOCORAN DATA PRIBADI MELALUI MEDIA SOSIAL WHATSAPP - Chaerudin; Hery Chariansyah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Advancements in information and communication technology have brought about significant changes in society. As a digital communication-based social media platform, WhatsApp plays a crucial role in the exchange of personal information. However, the increased use of WhatsApp is directly proportional to the rising risk of personal data breaches. This study aims to analyze the protection of victims of personal data breaches occurring via WhatsApp, examine the relationship between influencing and affected variables, and correlate empirical conditions (*das sein*) with normative conditions (*das sollen*). The study employs a normative legal research method utilizing statutory and conceptual approaches. The findings indicate that although Indonesia has enacted Law Number 27 of 2022 concerning Personal Data Protection, the implementation of legal protection for victims of data breaches still faces various obstacles regarding both law enforcement and public awareness.